Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species - Shih, Hsi-Te; Lee, Jung-Hsiang; Ho, Ping-Ho; Liu, Hung-Chang; Wang, Chia-Hsiang; Suzuki, Hiroshi; Teng, Shao-Jyun (Zootaxa, 2016)
The fiddler crabs, genus Uca Leach, 1814 (Decapoda, Ocypodidae) of Taiwan, including the offshore islands of Penghu (Pescadores), Kinmen (Quemoy), Matsu (Matzu), and Dongsha (Pratas), are revised, with the recognition of five subgenera and 15 species, viz. Uca (Austruca) Bott, 1973: U. lactea (De Haan, 1835), U. perplexa (H. Milne Edwards, 1837), U. triangularis (A. Milne-Edwards, 1873); U. (Gelasimus) Latreille, 1817: U. borealis Crane, 1975, U. jocelynae Shih, Naruse & Ng, 2010, U. tetragonon (Herbst, 1790), U. vocans (Linnaeus, 1758); U. (Paraleptuca) Bott, 1973: U. crassipes (White, 1847), U. splendida (Stimpson, 1858); U. (Tubuca) Bott, 1973: U. acuta (Stimpson 1858), U. arcuata (De Haan, 1835), U. coarctata (H. Milne Edwards, 1852), U. dussumieri (H. Milne Edwards, 1852), U. paradussumieri (Bott, 1973); and U. (Xeruca) Shih, 2015: U. formosensis Rathbun, 1921. Among them, U. acuta, U. paradussumieri, and U. vocans are confirmed to be distributed in Taiwan. Uca formosensis is endemic to Taiwan. The Uca species of the main islands of Japan are also listed. Four species (U. arcuata, U. lactea, U. crassipes and U. borealis) are known, but the recent additional records of U. perplexa and U. vocans need further confirmation. Except U. acuta, U. borealis, U. formosensis, U. lactea, and U. paradussumieri, other 10 Taiwanese species can be found from the Ryukyus too. Only one endemic species, U. boninensis, is reported from the Ogasawara (Bonin) Islands. A key to the 18 species of Uca found in East Asia is also provided in this study.